Evaluation of ceramic marker for the treatment of ocular melanoma with proton therapy. (13th March 2017) - Saini, Jatinder; Bowen, Stephen R; James, Sara St; Wong, Tony; Bloch, Charles
Abstract: BioMarc Secure TM, a fiducial marker with ceramic core (zirconium oxide) and carbon coating, was evaluated for use in the localization and alignment of ocular melanoma targets using proton pencil beam scanning (PBS). Measurements and Monte Carlo (MC) simulations were performed to estimate the dose attenuation behind the marker. Imaging tests were performed to evaluate the visibility of marker for x-ray based alignment. An anthropomorphic phantom with implanted fiducial marker was scanned to obtain two-dimensional kilo-voltage (kV) x-ray and three-dimensional computed tomographic (CT) images. For dose shadow measurements, an in-house phantom was constructed using solid water, Styrofoam and EBT3 gafchromic film. Dose attenuation behind the marker was measured at multiple depths and for three cardinal orientations: parallel, perpendicular, and transverse. The measurements were performed at the proton pencil beam gantry at the Seattle Cancer Care Alliance Proton Therapy center. A beam model for pencil beam gantry was created in the validated MC simulation toolkit GATE (GEANT4 Applications for Tomographic Emission). MC simulations were set up to mimic the measurement geometry and dose attenuation behind the marker was studied for a single layer PBS beam. Additional simulations were performed in water using the clinical relevant spread out Bragg peak (SOBP) beam. Qualitative analysis of the planar kV images showed excellent visibility of marker. Reconstruction artifacts in the form of light and dark streaks were present on the CT images. The film and MC simulations showed significant dose attenuation behind the marker that worsened when marker was placed close to the distal edge. Dose shadows of up to 45% and range loss of up to 1.1 mm were seen behind the marker. The transverse marker orientation in the clinical SOBP beam showed dose reduction of up to 61% and range pull-back of 2.4 mm. The dose attenuation was found to be a function of marker orientation and location within the SOBP. The analysis showed that small volumes behind the marker can see severe under-dosing. This effect should be taken into account during the planning of treatment. Comparing the results of this study to published results for tantalum marker, the BioMarc Secure marker was found to be inferior due to its greater dose attenuation and extended dose shadow on larger underlying volume. Furthermore, its bigger physical size may mean more discomfort to patient.